Fundamentals of entrepreneurship / Azlin Shafinaz Arshad ... [et al.] - Arshad, Azlin Shafinaz; Kamall Khan, Yasmin; Zainal Abidin, Zanariah; Mohammad Kamaruddin, Laila; Syed Marzuki, Sharifah Zannierah (UiTM Press, 2022)
The Fundamentals of Entrepreneurship is the culmination of hard effort from a group of dedicated academicians from the Faculty of Business and Management, Universiti Teknologi MARA, Malaysia. The book is written to address the need for a comprehensive textbook in Introduction to Entrepreneurship at UiTM and also other higher institutions of education in Malaysia. The primary emphasis of this book is on the preparation of a Business Plan that is considered to be crucial when starting a business. This book is written based on local context with regards to business formation, regulations and support systems. The book is comprehensive, yet written in a simple and straightforward manner, benefitting readers from students, entrepreneurship trainers, start-up entrepreneurs, to the general public who are keen to further understand the process of starting a business and developing a viable Business Plan. The book consists of fourteen chapters and covers aspects of entrepreneurship from entrepreneurial motivation, creativity, business formation to a step-by-step guide in preparing a Business Plan. Moreover, this book also aims to inspire its readers, especially students to confidently explore the vast opportunities in entrepreneurship. The authors also would like to take the opportunity to thank all individuals and parties who have supported the publication of this book.